Athletic contests and individual robberies: an analysis based on hourly crime data. Issue 8 (13th February 2016) - Yu, Ya; Mckinney, C. Nicholas; Caudill, Steven B.; Mixon, Franklin G.
ABSTRACT: Using hourly data on individual robberies, this article employs a novel approach to investigate the relationship between athletic contests and individual robberies in Memphis, Tennessee, a well-known entertainment destination, with its iconic Beale Street locale, in the US. Empirical results indicate that home basketball games hosted by the NBA's Memphis Grizzlies and those hosted by the University of Memphis Tigers are associated with increases in individual robberies, while away games are not associated with such an increase. This finding is consistent with the hot spot theory of crime, as large numbers of individuals travel to the games, thus providing additional opportunities for crime.